An Integrated Paper‐Based Readout System and Piezoresistive Pressure Sensor for Measuring Bandage Compression. Issue 9 (15th September 2016) - Liana, Devi D.; Raguse, Burkhard; Gooding, J. Justin; Chow, Edith
Abstract : The treatment of venous leg ulcers is commonly performed through the use of compression bandaging. However, applying an effective pressure can be a challenge, even for an experienced nurse. In this work, a simple and portable integrated platform consisting of a piezoresistive pressure sensor, paper‐based electrochromic readout system and battery is developed to directly monitor the applied pressure. The pressure sensor is fabricated using a mixture of copper particles and polydimethylsiloxane and tuned to the desired pressure sensitivity via the addition of carbon paste. Since the sensor is to be incorporated within the bandage, an external electronic display is not practical and thus a lightweight, paper‐based readout system comprising an electrochromic coating of Prussian blue/polyaniline on top of segments of gold nanoparticle films connected via graphite resistive films is developed. The readout system functions by measuring changes in the voltage drop across the readout system due to changes in the resistance of the pressure sensor. This allows the applied pressure to be visualized by the number of gold nanoparticle segments that have changed color in the readout system. This work opens the door to a lightweight and low‐cost sensing approach for compression bandaging at home or in community locations. Abstract : An integrated pressure sensor, paper‐based readout display and battery for monitoring effective compression bandaging is developed. Through this approach, the pressure applied to a C:Cu:polydimethylsiloxane piezoresistive composite can be visualized electrochromically by counting the number of gold nanoparticle film segments that change color on the readout system, thus allowing measurement without a complicated external electronic display.